The Determinant On Earnings Persistence In Automotive Companies In Indonesia - Adibah Yahya; Saepul Hidayat (Kesatuan Press, 2020)
The purpose of this study was to determine the effect of the variable Current Ratio, Total Debt To Total Assets, Total Assets Turnover, Return On Assets, on earnings persistence. This study uses secondary data, namely the annual financial statements of automotive companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample selection uses a purposive sampling method. The data source is the financial ratios of automotive companies listed on the IDX. Methods of data analysis using the classic assumption test, multiple linear regression, T-test, F-test and the coefficient of determination. The results showed that partial earnings persistence expressed in financial ratios consisting of the Return On Assets (ROA) variable significantly affected earnings persistence, while the Current Ratio (CR), Total Debt To Total Asset (TDTA) and Total Assets Turnover (TATO) has no significant effect on earnings persistence. While the results of the study simultaneously stated in financial ratios consisting of CR, TDTA, TATO, and ROA independent variables stated that together the independent variables had no significant effect on earnings persistence. R Square value of 0.028 can be interpreted that CR, TDTA, TATO and ROA of 2,8% while the remaining 97,2% is influenced by other variables not examined. Keywords: Current Ratio, Total Debt To Total Assets, Total Assets Turnover, Return On Assets, Earnings Persistence